APLIKASI CEK BAYAR PAJAK KENDARAAN BERMOTOR SAMSAT JAWA TIMUR BERBASIS ANDORID - Subagiyo -; Muhyiddin Zainul Arifin; Agus Sifaunajah (SAINTEKBU, 2016)
Monopoly check is a monopoly that was taken from the owner and authority vehicle that was registered in their territory. Android is operation system for a mobile phone with the basic linux to reserve opening platform for advance to make their application. The researcher using research method to make the last report is observation with the data to use in his report. Interview with the session asking question for the official samsat gresik to get more detail payment. The researcher are getting reference from the books that can applied in this research.From the result findings that was the researcher doing, the researcher make â€œCheck Application Of Monopoly Payment Vehicle Through The Basic Androidâ€. His research applied counting of monopoly check vehicle into sets agency media android. Besides that tools was used into make application is android studio as IE legality to develop android and java application as language program that was used. For the expectation, into the result finding is to make user of this application they are getting easy to get more information about the payment of monopoly vehicle.Â Keyword : monopoly, vehicle, java, androidÂ